Contributions of Sufism to The Maintenance Global Peace - Ismail Adaramola Abdul Azeez; Muhammad Afifuddin (Fakultas Agama Islam Universitas Billfath, 2023)
Since the inception of consciousness, humans have sought methods to explore their individual existence. Sufism is widely regarded as the most embraced spiritual path for attaining the realization of Allah, with the aim of fostering love, harmony, and peace within society. This study specifically aims to examine the contributions of Sufis in the maintenance of global peace. Sufism has endeavored to unite diverse groups across the world, with the objective of establishing a practical roadmap to peace. This objective is of great importance as society is currently experiencing increasingly tumultuous times, necessitating the establishment of a sustainable framework for peaceful cooperation and humanity. It is widely acknowledged that Sufism has the potential to cultivate worldwide peace, as it offers an impartial approach that fosters a peaceful environment based on tolerance, empathy, and serenity. Contrary to Western misunderstandings, Sufism is open to all individuals regardless of their social class, race, ethnicity, caste, or creed. The essence of Sufism lies in the love for Allah and the belief in the ultimate authority of Allah